M92. THE OVERLAP BETWEEN PSYCHOTIC SYMPTOMS, SUBSTANCE USE, AND ADVERSITY HISTORY: A SYSTEMATIC REVIEW. (18th May 2020) - Patterson, Victoria; Pencer, Alissa; Tibbo, Philip
Abstract: Background: Research has found that adversity and substance use individually influence the onset of psychosis and its clinical outcomes, though there has been little examination of a potential three-way interaction. An estimated 30–75% of individuals with psychosis have experienced at least one adverse event that predates their psychotic symptoms, and substance misuse is estimated to exceed 55% in individuals with psychosis. The current systematic review is the first attempt to review the temporal ordering of adversity, psychosis, and substance misuse, as well as examining the effect of type (e.g., type of adversity, type of substance) on the association between these variables. Methods: Following PRISMA guidelines, a comprehensive search strategy and review of studies against strict inclusion and exclusion criteria was completed. Studies published between 2000 and 2020 were included from PsycINFO, PubMed, CINAHL, EMBASE, Scopus, Web of Science, and the grey literature. Inclusion criteria, all of which must be met within a single study, included a diagnosed psychotic disorder, experiencing at least one adverse event, and current or past problematic substance use (i.e., substance misuse). High-risk and prodromal studies were excluded. We used search term combinations such as (schizophrenia OR schizoaffective) AND (adversity or trauma OR abuse) AND ("substance abuse" OR cannabis OR cocaine). Results: Our initial search found 7, 183 papers examining psychotic disorders, substance misuse, and adversity. Preliminary results for included studies indicate that 13 studies met criteria for inclusion. Across studies, the prevalence of experiencing at least one adverse event ranged from 24.8 to 100%, with significant variation in rates among studies due to variance in definitions of adversity, instruments used, and types of adverse events assessed. It is noteworthy that people with a psychotic disorder and a substance use disorder experienced more adverse events compared to people with a psychotic disorder and no substance use disorder. Moreover, individuals with a psychotic disorder, substance misuse, and a history of adversity are more likely to experience reduced functional outcomes, lower rates of remission of psychotic symptoms, and increased post-traumatic stress symptoms and diagnoses. Across studies, adversity appeared to precede substance misuse, which preceded psychotic disorder onset. Discussion: Our results suggest that individuals affected by psychotic disorders, substance misuse, and a history of adversity fare worse than those without a history of adversity, even once enrolled in a treatment program for psychosis. Moreover, adversity appeared to precede both substance misuse and psychotic disorders, however, the role of additional adverse events within this relationship was not well-studied and should be examined in the future. Findings suggest that assessing for substance use and a history of adversity within psychosis treatment programs is a critical first step in the recovery for people affected by these psychiatric comorbidities and specific treatment options addressing these factors would be critical for recovery. Moreover, treatment options should be capable of targeting maintenance mechanisms (e.g., avoidance, hopelessness) shared by all three constructs to provide an integrated treatment approach.